2017
DOI: 10.1017/ice.2017.236
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Distribution and Antimicrobial Resistance Among Pediatric Healthcare-Associated Infections Reported to the National Healthcare Safety Network, 2011–2014

Abstract: OBJECTIVETo describe pathogen distribution and antimicrobial resistance patterns for healthcare-associated infections (HAIs) reported to the National Healthcare Safety Network (NHSN) from pediatric locations during 2011–2014.METHODSDevice-associated infection data were analyzed for central line-associated bloodstream infection (CLABSI), catheter-associated urinary tract infections (CAUTI), ventilator-associated pneumonia (VAP), and surgical site infection (SSI). Pooled mean percentage resistance was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
103
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 34 publications
3
103
4
2
Order By: Relevance
“…1 Decreasing neonatal nasal S. aureus burden, through decolonization, reduces risk of nosocomial infections. 11 In this retrospective study, we demonstrated that more than a third of hospitalized neonates developed recurrent S. aureus nasal colonization after a mupirocin-based decolonization treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Decreasing neonatal nasal S. aureus burden, through decolonization, reduces risk of nosocomial infections. 11 In this retrospective study, we demonstrated that more than a third of hospitalized neonates developed recurrent S. aureus nasal colonization after a mupirocin-based decolonization treatment.…”
Section: Discussionmentioning
confidence: 99%
“…1 Staphylococcus species, which constitute early components of the neonatal skin, nares and gastrointestinal microbiomes, continue to be responsible for the majority of neonatal late-onset sepsis (LOS). 25 S. aureus colonization often precedes invasive infections such as central line associated blood stream infections (CLABSI), bacteremia, pneumonia, and on rare occasions meningitis, putting premature infants at risk for long term neurological sequelae.…”
Section: Introductionmentioning
confidence: 99%
“…It could also help in the recognition of prevalent pathogens based on the site of infection, in the optimization of resources, and in the stimulation of rational antibiotic use, while contributing to multimodal strategies aimed at reducing MDR rates 6 . Wellstructured nosocomial infection surveillance systems, which are governmental and non-governmental initiatives, are described around the world [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…We use Enterococcus faecalis as a model organism to study the interactions of CRISPR-Cas systems with conjugative plasmids. E. faecalis is a gram-positive bacterium, a native inhabitant of the mammalian intestine (5), and an opportunistic pathogen that is among the leading causes of hospital-acquired infections (HAIs) in the United States (6, 7). E. faecalis strains causing HAIs possess unique characteristics relative to strains that normally colonize the human intestine.…”
Section: Introductionmentioning
confidence: 99%